2020
DOI: 10.3390/molecules25122914
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fundamental Evaluation of Radioiodinated Rociletinib (CO-1686) as a Probe to Lung Cancer with L858R/T790M Mutations of Epidermal Growth Factor Receptor (EGFR)

Abstract: Rociletinib (CO-1686), a 2,4-diaminopyrimidine derivative, is a highly potent tyrosine kinase inhibitor (TKI) that acts on epidermal growth factor receptor (EGFR) with L858R/T790M mutations. We supposed radioiodinated CO-1686 would function as a useful tool for monitoring EGFR L858R/T790M mutations. To aid in patient selection before therapy with EGFR-TKIs, this study aimed to develop a 125I-labeled derivative of CO-1686, N-{3-[(2-{[4-(4-acetylpiperazin-1-yl)-2-methoxyphenyl]amino}-5-(trifluoromethyl)pyrimidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…The log p value for [ 77 Br]9 was 1.72 ± 0.21, which indicates that [ 77 Br]9 has appropriate lipophilicity for passive membrane penetration. The log p value of [ 77 Br]9 was significantly lower than that of [ 125 I]ICO1686, which was 1.84 ± 0.01 (p = 0.0097) [9]. This result is consistent with the reverse-phase HPLC analysis, in which the retention time of [ 77 Br]9 was shorter than that of [ 125 I]ICO1686.…”
Section: Determination Of Partition Coefficientsupporting
confidence: 81%
See 4 more Smart Citations
“…The log p value for [ 77 Br]9 was 1.72 ± 0.21, which indicates that [ 77 Br]9 has appropriate lipophilicity for passive membrane penetration. The log p value of [ 77 Br]9 was significantly lower than that of [ 125 I]ICO1686, which was 1.84 ± 0.01 (p = 0.0097) [9]. This result is consistent with the reverse-phase HPLC analysis, in which the retention time of [ 77 Br]9 was shorter than that of [ 125 I]ICO1686.…”
Section: Determination Of Partition Coefficientsupporting
confidence: 81%
“…In our previous study, an in vitro kinase inhibition assay with ICO1686 and CO-1686 showed their high selectivity toward double mutations EGFR L858R/T790M compared with that toward wild-type EGFR [ 9 ]. Therefore, we conducted a further study by designing and synthesizing radiobrominated [ 77 Br] 9 as a surrogate of [ 76 Br] 9 , which can be used as a molecular imaging agent for EGFR L858R/T790M because bromine could be a bioisostere of iodine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations